Growth hormone (GH) replacement in hypopituitary adults with GH deficiency evaluated by a utility-weighted quality of life index: a precursor to cost–utility analysis - Kołtowska-Häggström, Maria (Blackwell Publishing Ltd, 2008)
OBJECTIVES: To examine quality of life (QoL) measured by a utility-weighted index in GH-deficient adults on GH replacement and analyse the impact of demographic and clinical characteristics on changes in utilities during treatment. DESIGN: Utilities for items in the QoL-Assessment of Growth Hormone Deficiency in Adults (QoL-AGHDA(utility)) were estimated based on data obtained from the general population in England and Wales (E&W). These estimates were used to calculate QoL changes in GH-treated patients and compare these with normative population values. PATIENTS: A total of 894 KIMS patients (53% women) from E&W were followed for 1 to 6 years. MEASUREMENTS: QoL-AGHDA(utility) at baseline and at the last reported visit, total QoL-AGHDA(utility) gain and QoL-AGHDA(utility) gain per year of follow-up. RESULTS: QoL-AGHDA(utility) in patients before GH treatment differed from the expected population values [0·67 (SD 0·174) vs. 0·85 (SD 0·038), P < 0·0001], constituting a mean deficit of –0·19 (SD 0·168). There was a difference in the mean QoL-AGHDA(utility) deficit for men [–0·16 (SD 0·170)] and women [–0·21 (SD 0·162)] (P < 0·001). The main improvement occurred during the first year of treatment [reduction of a deficit to –0·07 (SD 0·163) (P < 0·001) in the total cohort]; however, patients’ utilities remained lower than those recorded for the general population during subsequent follow-up (P < 0·001). Despite an observed impact of age, primary aetiology, disease onset and comorbidities on QoL-AGHDA(utility), all patients showed a similar beneficial response to treatment. CONCLUSIONS: QoL-AGHDA(utility) efficiently monitors treatment effects in patients with GHD. The study confirmed the QoL-AGHDA(utility) deficit before treatment and a similar QoL-AGHDA(utility) gain observed after commencement of GH replacement in all patients.